2018
DOI: 10.1159/000484206
|View full text |Cite
|
Sign up to set email alerts
|

Response of Retinoic Acid in Patients with Radioactive Iodine-Refractory Thyroid Cancer: A Meta-Analysis

Abstract: Purpose: The purpose of this study was to evaluate the response of retinoic acid (RA) in radioactive iodine (RAI)-refractory differentiated thyroid cancer (DTC). Methods: Systematic searches of MEDLINE (from inception to December 2016) and of EMBASE (from inception to December 2016) were performed for English-language publications on thyroid cancer treated with RA. Studies were classified according to the response criteria used: (1) 123I or 131I whole body scintigraphy (WBS), (2) serum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…A recent meta-analysis on retinoids in RAIR-DTC reported a pooled effect of 27.6% for increased radioiodine uptake and 17% for tumor response by RECIST criteria (Pak et al 2018) In these phase 1 and 2 trials, the 131I diagnostic WBS showed restoration of faint radioiodine uptake after various time periods of treatment in two out of six evaluable patients for the phase 1 study and 2 out of 16 patients for the phase 2. In the phase 2 trial (Sherman et al 2013), the faint radioiodine uptake observed on the diagnostic WBS was confirmed on the therapeutic WBS but without longterm benefit from the treatment.…”
Section: Retinoic Acidmentioning
confidence: 97%
“…A recent meta-analysis on retinoids in RAIR-DTC reported a pooled effect of 27.6% for increased radioiodine uptake and 17% for tumor response by RECIST criteria (Pak et al 2018) In these phase 1 and 2 trials, the 131I diagnostic WBS showed restoration of faint radioiodine uptake after various time periods of treatment in two out of six evaluable patients for the phase 1 study and 2 out of 16 patients for the phase 2. In the phase 2 trial (Sherman et al 2013), the faint radioiodine uptake observed on the diagnostic WBS was confirmed on the therapeutic WBS but without longterm benefit from the treatment.…”
Section: Retinoic Acidmentioning
confidence: 97%
“…RA is the bioactive metabolite of vitamin A and plays a critical role in cellular differentiation during mammalian development. RA indeed may increase the expression of NIS mRNA in human FTC cells (Schmutzler et al 2002, Lan et al 2017a; however a recent meta-analysis reported that only a minority of patients with RAI-refractory DTC responded to RA treatment (Pak et al 2018). This poor response might be explained by the fact that RA treatment induces growth inhibition through retinoic acid receptor beta in cells where it is expressed, rather than through an increase of NIS at the plasma membrane (Elisei et al 2005).…”
Section: :11mentioning
confidence: 99%
“…Unfortunately, despite the interesting scientific basis, no studies have shown a definitive usefulness of vitamin A in thyroid cancer. Furthermore, one of the most recent reviews on this topic showed that only a minority of patients with RAI-R differentiated thyroid cancer respond well to retinoid treatment ( 54 ).…”
Section: Vitamin a And Thyroid Cancermentioning
confidence: 99%